Quantitative measures of health policy implementation determinants and outcomes: a systematic review - Peg Allen; Meagan Pilar; Callie Walsh-Bailey; Cole Hooley; Stephanie Mazzucca; Cara C. Lewis; Kayne D. Mettert; Caitlin N. Dorsey; Jonathan Purtle; Maura M. Kepper; Ana A. Baumann; Ross C. Brownson (Implementation Science, 2020)
Abstract Background Public policy has tremendous impacts on population health. While policy development has been extensively studied, policy implementation research is newer and relies largely on qualitative methods. Quantitative measures are needed to disentangle differential impacts of policy implementation determinants (i.e., barriers and facilitators) and outcomes to ensure intended benefits are realized. Implementation outcomes include acceptability, adoption, appropriateness, compliance/fidelity, feasibility, penetration, sustainability, and costs. This systematic review identified quantitative measures that are used to assess health policy implementation determinants and outcomes and evaluated the quality of these measures. Methods Three frameworks guided the review: Implementation Outcomes Framework (Proctor et al.), Consolidated Framework for Implementation Research (Damschroder et al.), and Policy Implementation Determinants Framework (Bullock et al.). Six databases were searched: Medline, CINAHL Plus, PsycInfo, PAIS, ERIC, and Worldwide Political. Searches were limited to English language, peer-reviewed journal articles published January 1995 to April 2019. Search terms addressed four levels: health, public policy, implementation, and measurement. Empirical studies of public policies addressing physical or behavioral health with quantitative self-report or archival measures of policy implementation with at least two items assessing implementation outcomes or determinants were included. Consensus scoring of the Psychometric and Pragmatic Evidence Rating Scale assessed the quality of measures. Results Database searches yielded 8417 non-duplicate studies, with 870 (10.3%) undergoing full-text screening, yielding 66 studies. From the included studies, 70 unique measures were identified to quantitatively assess implementation outcomes and/or determinants. Acceptability, feasibility, appropriateness, and compliance were the most commonly measured implementation outcomes. Common determinants in the identified measures were organizational culture, implementation climate, and readiness for implementation, each aspects of the internal setting. Pragmatic quality ranged from adequate to good, with most measures freely available, brief, and at high school reading level. Few psychometric properties were reported. Conclusions Well-tested quantitative measures of implementation internal settings were under-utilized in policy studies. Further development and testing of external context measures are warranted. This review is intended to stimulate measure development and high-quality assessment of health policy implementation outcomes and determinants to help practitioners and researchers spread evidence-informed policies to improve population health. Registration Not registered